(untitled) (International Journal of Food and Nutritional Sciences, 2023)
White Gut Disease, also known as White Feces Syndrome (WFS), is a prevalent and economically significant condition affecting the Pacific white shrimp (Litopenaeus vannamei) aquaculture industry in worldwide. This condition is distinguished by the presence of pale or whitish excrement in shrimp that are affected, along with gastrointestinal problems. The exact etiology of white gut disease in L.vannamei remains unclear, although various factors have been implicated. The present study suggests that the disease may be multifactorial, involving a combination of infectious agents, dietary imbalances, environmental stressors, and improper management practices. White gut disease has significant negative impacts on shrimp health and productivity. Infected shrimp may exhibit reduced feed intake, growth retardation, and increased mortality rates. The WFS disease also has economic implications, leading to financial losses for shrimp farmers due to decreased production and increased treatment costs. The present study reveals that, the role of herbal supplements Allium sativum and Curcuma longa on improving growth and gut health of the shrimp L.vannamei in the culture pond environment.